The role of women and minors in radicalisation processes and jihadist extremism - Moreno Ruiz, Raúl (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2025)
The role of women and under-ages has been evolving and becoming increasingly important in the context of the global strategy of terrorist organizations to achieve their ultimate objectives, these being the fundamentalist execution of Islamic Law or “Sharia” and establishing the Caliphate. universal. Thus, women have consecrated a leading role, both on the active and passive level, for the consolidation and expansion of the jihadist ideology, materializing both at the logistical level and at the level of execution of violent actions, recruitment and radicalization processes. of followers, as well as glorification and financing of these terrorist organizations, crucial functions for the ultimate success of the armed group.